2013
DOI: 10.1139/apnm-2012-0230
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of organic purple grape juice on exhaustive exercise

Abstract: This study aimed to assess the potential protective effect of organic purple grape juice (PGJ) on oxidative stress produced by an exhaustive exercise bout in rats. To test this hypothesis, rats were acutely treated with organic PGJ (Vitis labrusca) and subsequently submitted to an exhaustive exercise bout. Parameters of oxidative stress, such as thiobarbituric acid reactive species (TBARS) levels, 2',7',-dichlorofluorescein diacetate (DCFH-DA) oxidation, and nonprotein sulfhydryl levels (NP-SH) in the brain, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“… Huang et al (2013) reported that physical exercise induced oxidative stress which could cause damage to muscle and liver tissues ( Huang et al, 2013 ). Dalla Corte et al (2013) demonstrated that elevation of oxidative damage markers in the brain, skeletal muscle, and blood after exhaustive exercise ( Dalla Corte et al, 2013 ). The results of all these studies investigating effects of exercise in the literature demonstrated is conflicted.…”
Section: Discussionmentioning
confidence: 99%
“… Huang et al (2013) reported that physical exercise induced oxidative stress which could cause damage to muscle and liver tissues ( Huang et al, 2013 ). Dalla Corte et al (2013) demonstrated that elevation of oxidative damage markers in the brain, skeletal muscle, and blood after exhaustive exercise ( Dalla Corte et al, 2013 ). The results of all these studies investigating effects of exercise in the literature demonstrated is conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on laboratory animals have suggested that acute aerobic exercise increases oxidative stress levels not only in blood but also in tissues such as skeletal muscle and the brain, heart, lungs, liver, kidneys, and spleen [ 54 , 55 , 56 , 57 , 58 , 59 ]. It must be noted that, as Liu et al, demonstrated in 2000, the oxidative stress response to acute aerobic exercise is tissue specific [ 60 ].…”
Section: Exercise-induced Oxidative Stressmentioning
confidence: 99%
“…On the other hand, under HIE training, ROS production may be strongly and persistently increased, and the antioxidant response may not be effective to reset the system to the original levels of brain redox homeostasis [3]. In fact, HIE has been shown to induce oxidative stress and increase lipid peroxidation in a mouse brain [18,53]. In view of these contradictory results in the literature, our findings agree with some of the aforementioned studies in that no significant evidence was observed in brain TBARs levels after an HIE protocol.…”
Section: High-intensity Exercise Anabolic Androgenic Steroids and Brmentioning
confidence: 99%